Serum calcium levels and the risk of sarcopenia in young adults: insights from NHANES 2011–2018 - Jiang, Junliang; Chen, Ge; Li, Yonggang; Zhao, Qinggang; Chen, Zhong (Frontiers in Nutrition, 2025)
BackgroundSarcopenia, the accelerated loss of muscle mass and function, is commonly associated with aging, especially in older adults. While low serum calcium has been linked to muscle loss in individuals over 50, its relationship with sarcopenia in younger adults (20–60 years) is unclear. This study examines this association using data from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018.MethodsThis population-based, cross-sectional study analyzed participants aged 20–60 from NHANES 2011–2018. Individuals with missing data were excluded. Sarcopenia was assessed using appendicular skeletal muscle (ASM) measured by dual-energy X-ray absorptiometry, defined by ASM/BMI or ASM/Weight. Multiple logistic regression and stratified analyses were used to explore the correlation between serum calcium levels and sarcopenia prevalence.ResultsAmong 7,309 adults, 578 (7.91%) had sarcopenia by ASM/BMI and 1,363 (18.65%) by ASM/Weight. Higher serum calcium levels were significantly associated with a lower risk of sarcopenia (ASM/BMI: OR 0.07, 95% CI 0.02–0.20; ASM/Weight: OR 0.09, 95% CI 0.04–0.19). The trend was consistent across age, gender, education, poverty income ratio, and race, with some exceptions.ConclusionThis study highlights a negative association between serum calcium and sarcopenia risk in young and middle-aged adults, suggesting that calcium interventions could be beneficial in preventing sarcopenia in this population. However, the cross-sectional design precludes any inference of causality, and further longitudinal studies are warranted to confirm these findings.